Phishing – challenges and solutions. Issue 1 (January 2018) - Vayansky, Ike; Kumar, Sathish
Abstract : Phishing is a major threat to all Internet users and is difficult to trace or defend against since it does not present itself as obviously malicious in nature. In today's society, everything is put online and the safety of personal credentials is at risk. Phishing can be seen as one of the oldest and easiest ways of stealing information from people and it is used for obtaining a wide range of personal details. It also has a fairly simple approach – send an email, email sends victim to a site, site steals information.